Positive ionic conduction of mayenite cement Ca12Al14O33/nano-carbon black composites on dielectric and thermoelectric properties - Chalermpol Rudradawong; Mettaya Kitiwan; Takashi Goto; Chesta Ruttanapun (My University, 2019)
Mayenite Ca12Al14O33/nano-carbon black composites (C12A7/nCB) were investigated regarding the mechanism of oxygen ion vacancy in the extra cage framework of positive ionic transport in thermoelectric and dielectric properties. The oxygen ion vacancy in C12A7/nCB composites was produced from C12A7 composited with nano-carbon back (nCB) for 0, 1, 3, 5 and 10 wt% by the rapid spark plasma sintering. The C12A7/nCB samples were characterised by X-ray diffraction (XRD), UV–vis spectroscopy, Raman spectroscopy, Scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and UV–vis spectroscopy. The O−2 ions vacancy was confirmed by Raman spectrum. The positive ionic conduction was verified by the positive sign of Seebeck coefficient. The ionic conductivity was in order 5 S/cm of C12A7/nCB of 10 wt% content. The thermal conductivity was reduced by the effects of the O−2 ions vacancy as point defect. The ZT for thermoelectric materials of C12A7/nCB of 10 wt% content were in a range from 0.01 × 10−3 to 0.16 × 10−3, respectively. Positive ion conduction of C12A7/nCB composites resulting from oxygen ion vacancy occupying in extra framework affected to enhance dielectric constant, Seebeck coefficient, electrical conductivity and reduce thermal conductivity.
Keywords: Spark Plasma Sintering; Ammonia Synthesis and Nitrogen Reduction